University students adaptation to the Chinese culture : a case study of Middle East and North Africa (MENA) University students in China - Shuo, Zhao; al-Nahdi, Yousef Ali Ahmed Saleh; Fuzhen, Susan Si; Firdous, Tehmina (Penerbit Universiti Kebangsaan Malaysia, 2023)
This study explores the adaptation of Arab students to Chinese culture, using MENA students as examples. MENA students are from the Middle East and North Africa (Arabic is their mother tongue and is commonly referred to as “Arabs”). The purpose of their visit is to pursue their studies in China and to adopt the Chinese lifestyle. We examine how they integrated Chinese culture into their culture and vice versa to better understand their adaptation to the Chinese cross-culture. Their perception of Chinese society and lifestyle differs from their own. We conducted a survey comprising forty-one closed questions and one open-ended question to examine fifty-five MENA students studying in mainland China. Regardless of their backgrounds, the results suggest that their adaptation to Chinese culture appears to include adhering to Chinese etiquette, becoming close to the way of life, examining the development of Technology, and attempting to share Chinese development perspectives with their own cultures. In contrast to their own culture, they display a high degree of adaptability to the conditions and rules of Chinese society with 89% of total participants. Aside from displaying cultural diversity, they also highlight language proficiency challenges, impressions of the culture, and wonders of the host country.